Evaluation of Patients’ Received Doses in Chest CT Scan Protocols for COVID-19 Diagnosis - Sadegh Shurche; Tinoosh Almasi; Maryam Tima; Nima Rostampour (Frontiers in Biomedical Technologies)
Purpose: This study aims to investigate and compare the doses received by Corona Virus Disease (Covid-19) patients on Computed Tomography (CT) scans by changing the scan parameters to diagnose the disease and evaluate its course and effects.